Mapping value co-creation in studies on higher education - Loor Ávila, Katty (2023)
The co-creation of value in higher education is a concept that focuses on the process of active and participatory collaboration between all the actors involved in the university system, in order to generate value together. The objective of this research was to carry out a detailed mapping of the corpus of knowledge related to the co-creation of value in higher education according to studies of the Web of Science between the period 2012-2022. A descriptive and retrospective investigation was carried out, based on the exploratory systematic review methodology, in publications selected according to relevance and relevance criteria. The results of the analysis helped to identify trends and patterns of co-creation of value in the university environment, evidencing that quality, satisfaction and commitment are emerging axes among researchers in the field and who study the processes of joint creation of value. The research proposes some areas of analysis and lines of specialized research that may be important to address in future work. Key issues that emerge from research with the purpose of strengthening the institutional management of universities.